Immigrants and Socio-Cultural Changes in the Population of Contemporary German-Speaking Switzerland - Lesław Tobiasz (Rocznik Polsko-Niemiecki, 2015)
The author analyses the problems of socio-cultural changes in the German-speaking population of Switzerland. In particular, he focuses on the processes that result from the presence of numerous immigrant communities. The analysis relates mainly to the period a er the collapse of communism in Central and Eastern Europe. At the same time, the transformations in the German-speaking population of Switzerland are shown on the background of historical processes that have shaped the Swiss multiculturalism and multilingualism. The analysis takes into account the complex interactions between different multilingual areas of the country and external impacts resulting from socio-cultural processes outside its borders, especially in Germany. The German-speaking part of the multicultural Swiss Confederation is currently experiencing a period of rapid social changes. These changes relate to the sphere of culture, language, economy and politics. The German-speaking Swiss are trying to redefine their identity and role in the world, full of different challenges and threats. One of them is the approach to immigrants and the culture they represent. It can be assumed that in the next few years, the Swiss – in fear of the inflow of other cultures – will seek to limit immigration processes, while strengthening the processes for the effective integration of newcomers in the multicultural society.